Strategizing desire. Issue 1 (March 2023) - Schmid, Benedikt
This contribution comments and builds on Callum Sutherland's exploration of the spatial imaginaries latent in the thinking of the late Mark Fisher. Appreciating Sutherland's rich account on the nexus of space, (post-) capitalism, culture, and desire – as developed through a spatial reading of Fisher – I suggest the broadening of such a project to include a less prominent part of Fisher's work, namely his theorization of organization and strategy. Outlining four strategic orientations that thread through Fisher's work – 'mobilization of desire', 'institutional memory', 'creative freedom', and 'future orientation' – I discuss Fisher's take on postcapitalist strategies alongside the spatial–temporal imaginaries carved out by Sutherland.